Asymmetric public diplomacy : the King Abdullah Scholarship Programme in Saudi Arabia - Bouchaib Silm (Nanyang Technological University, 2021)
This thesis proposes to unpack meaningful distinctive features of the public diplomacy dynamics unfolding between Saudi Arabia and the United States in the post 9/11 period. This investigation aims to offer additional insights to understand the role and the conduct of public diplomacy in international relations by focusing on the perspective of a non-western middle power. Its main contribution to the study of this academic field rests on departing from the classic understanding of public diplomacy as a ‘one-way’ flow to offer instead, an understanding and theoretical insights of the particularities of public diplomacy conducted in asymmetric contexts.